Anisotropic turbulent viscosity and large-scale motive force in thermally driven turbulence at low Prandtl number - Mizerski, K.A. (Archives of Mechanics, 2022)
The fully developed turbulent Boussinesq convection is known to form large-scale rolls, often termed the ‘large-scale circulation’ (LSC). It is an interesting question how such a large-scale flow is created, in particular in systems when the energy input occurs at small scales, when inverse cascade is required in order to transfer energy into the large-scale modes. Here, the small-scale driving is introduced through stochastic, randomly distributed heat source (say radiational). The mean flow equations are derived by means of simplified renormalization group technique, which can be termed a ‘weakly nonlinear renormalization procedure’ based on consideration of only the leading order terms at each step of the recursion procedure, as full renormalization in the studied anisotropic case turns out unattainable. The effective, anisotropic viscosity is obtained and it is shown that the inverse energy cascade occurs via an effective ‘motive force’ which takes the form of transient negative, vertical diffusion.